Accuracy and reliability of voxel-based dentoalveolar registration (VDAR) in orthognathic surgical patients: a pilot study with two years' follow-up. Issue 4 (May 2021) - Shujaat, S.; Shaheen, E.; Politis, C.; Jacobs, R.
Abstract: The purpose of this study was to validate the applicability of using maxillary voxel-based dentoalveolar registration (VDAR) at long-term follow up in orthognathic surgical patients. A retrospective sample of 25 patients (skeletal class II or III) who underwent bimaxillary orthognathic surgery was recruited and divided into two groups. Group A included 15 patients (seven females, eight males, mean (SD) age 25.8 (14.4) years) with unrestored dentition and group B involved 10 patients (five females, five males, mean (SD) age: 26.2 (11.9) years) with dental restorative treatment. Postoperative cone-beam computed tomography (CBCT) scans were acquired at four time-points, one to six weeks (T1), six months (T2), one year (T3) and two years (T4). Voxel- based registration was applied using the cranial base and then complete dental segment with part of the alveolar bone at T1-T2, T1-T3 and T1-T4 time-intervals. The translational and rotational accuracy and reproducibility of the registered maxillary segment was evaluated at these three intervals by analysing the transformation matrix using singular value decomposition. All translational and rotational measurements showed excellent reliability in both groups without any significant difference. The combined translational and rotational difference was found to be within the clinically acceptable range of 2 mm and 4°. The VDAR was found to be accurate and reliable to be utilised for a long-term skeletal follow-up in orthognathic surgical patients.